2017
DOI: 10.3390/rs9020101
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Ocean Tide Loading in Differential InSAR Measurements

Abstract: Ocean tide loading (OTL) causes crustal displacements in coastal regions, and the relative variation of these ground displacements may reach several centimeters across differential interferometric synthetic aperture radar (DInSAR) interferograms. However, orbit errors seriously affect the analysis of long-wavelength crustal deformation signals such as the OTL effect because of their similar signatures in DInSAR interferograms. To correct the orbit errors, we used a linear surface model to model the relative di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…A predicted differential InSAR study has shown that OTL displacement is comparable to both InSAR accuracy and displacement rates for targets near coastlines with a predicted OTL displacement gradient of 3 cm per 100 km till 200 km away from the coast [54]. Another study eliminates OTL effect in Differential InSAR interferogram using FES2004 tide model after the estimation of orbit errors using GPS precise point positioning (PPP) [55]. However, GPS stations are not usually available and the global ocean models are not always accurate in offshore areas due to complicated coastline and seafloor relief [56].…”
Section: Seasonal Displacements and Tidal Levelsmentioning
confidence: 99%
“…A predicted differential InSAR study has shown that OTL displacement is comparable to both InSAR accuracy and displacement rates for targets near coastlines with a predicted OTL displacement gradient of 3 cm per 100 km till 200 km away from the coast [54]. Another study eliminates OTL effect in Differential InSAR interferogram using FES2004 tide model after the estimation of orbit errors using GPS precise point positioning (PPP) [55]. However, GPS stations are not usually available and the global ocean models are not always accurate in offshore areas due to complicated coastline and seafloor relief [56].…”
Section: Seasonal Displacements and Tidal Levelsmentioning
confidence: 99%
“…Lei et al (2017) claimed deformation observations were improved, but no details of the InSAR processing were given. Peng et al (2017) relied on GPS to remove a bilinear ramp but ignored tropospheric delay effects which could easily mask the OTL signal. Their interferograms also contained only small OTL signals compared with other error sources such as orbital errors which dominated.…”
Section: Introductionmentioning
confidence: 99%
“…The OTL effect needs to be corrected in a differential InSAR interferogram due to the fact its spatial variation can reach the cm/100km scale. Previous studies have demonstrated that OTL displacements in differential InSAR interferogram are non-linear and should be removed by the use of an ocean tide models [9,10]. In recent years, researchers have established a series of ocean tide models, such as NAO99b [11], FES2014b [12], EOT11a [13], and TPXO8 [14].…”
Section: Introductionmentioning
confidence: 99%